Normal liver stiffness and influencing factors in healthy children: An individual participant data meta‐analysis. (28th October 2020) - Li, Darrick K.; Khan, Muhammad Rehan; Wang, Zhen; Chongsrisawat, Voranush; Swangsak, Panida; Teufel‐Schäfer, Ulrike; Engelmann, Guido; Goldschmidt, Imeke; Baumann, Ulrich; Tokuhara, Daisuke; Cho, Yuki; Rowland, Marion; et al.
Abstract: Background & Aims: Although transient elastography (TE) is used to determine liver stiffness as a surrogate to hepatic fibrosis, the normal range in children is not well defined. We performed a systematic review and individual participant data (IPD) meta‐analysis to determine the range of liver stiffness in healthy children and evaluate the influence of important biological parameters. Methods: We pooled data from 10 studies that examined healthy children using TE. We divided 1702 children into two groups: ≥3 years (older group) and < 3 years of age (younger group). Univariate and multivariate linear regression models predicting liver stiffness were conducted. Results: After excluding children with obesity, diabetes, or abnormal liver tests, 652 children were analysed. Among older children, mean liver stiffness was 4.45 kPa (95% confidence interval 4.34‐4.56), and increased liver stiffness was associated with age, sedation status, and S probe use. In the younger group, the mean liver stiffness was 4.79 kPa (95% confidence interval 4.46‐5.12), and increased liver stiffness was associated with sedation status and Caucasian race. In a subgroup analysis, hepatic steatosis on ultrasound was significantly associated with increased liver stiffness. We define a reference range for normal liver stiffness in healthy children as 2.45‐5.56 kPa. Conclusions: We have established TE‐derived liver stiffness ranges for healthy children and propose an upper limit of liver stiffness in healthy children to be 5.56 kPa. We have identified increasing age, use of sedation, probe size, and presence of steatosis on ultrasound as factors that can significantly increase liver stiffness.